La città che viene - Scandurra, Enzo (Scienze del Territorio, 2015)
The first part of the paper describes the formation of the modern city, its representation and description through the narrative of the nineteenth century as well as the prominent features of this unprecedented agglomeration. The second part describes the great transformation that leads from modern city to what we call post-modern or contemporary city. The history of modern city, of its symbolic representation and grand narrative, stops when the phase of ‘classic’ capitalism gives way to the big neoliberal transformation in the economy. The third part describes the main features of this new urban environment and the dissolution of all what constituted the essence of the city. In the last part we analyze the social contradictions of this new development model and try to focus the elements from which it may be possible to trigger a process of re-building the city.